Datasets and models about the geophysical characterization of the Mt. Melbourne Volcanic Field (Northern Victoria Land, Antarctica) - Ghirotto, Alessandro; Armadillo, Egidio; Crispini, Laura; Zunino, Andrea; Caratori Tontini, Fabio; Ferraccioli, Fausto (Zenodo, 2022)
Supplementary materials about the geophysical characterization of the Mt. Melbourne Volcanic Field